THE USE OF COLOR-CODED WRITING (CCW) ON ADJECTIVE ORDER - Arriyadhi, Nizamuddin; Sutapa, Gatot; Susilawati, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract: This research was conducted to prove how this technique could affect the students’ mastery in Adjective Order. This research is a Pre-Experimental research with the students of SMPN 10 Pontianak as the sample. The result of this research showed that this technique was effective to the students’ mastery in Adjective Order. This was proven by the computation of the t-value which was higher than the t-table, which means this technique was effective. Thus, this technique affected the students’ mastery in Adjective Order. This technique is recommended to be used in not only teaching writing, but also teaching reading and vocabulary.Keywords: Color-coded writing, adjectives, adjective order.